Gardenia jasminoides fruit extract alleviates non-steroidal anti-inflammatory drug-induced gastropathy in rats - Rinrada Worapongpaiboon; Kasiphak Kaikaew; Pornpen Werawatganone; Kanjana Somanawat; Nathawadee Lerttanatum; Naruemon Klaikeaw; Duangporn Werawatganon (BMC, 2024)
Abstract Background NSAID-induced gastropathy is a health burden that requires effective intervention. Among various prevention options, Gardenia jasminoides fruit extract (GJE) has demonstrated gastroprotective effects through anti-inflammatory pathways with a wide safety margin. However, the detailed molecular mechanisms of GJE regarding mucoprotective and anti-inflammatory effects remained to be explored. Therefore, we investigated the effects of GJE on NSAID-induced gastric injury in rats, focusing on the expression of the protective factors: prostaglandin E2 (PGE2) and mucin 5AC (MUC5AC), and the aggravating factors: inducible nitric oxide synthase (iNOS) and nuclear factor-κB (NF-κB). Methods Twenty-four male Sprague-Dawley rats were assigned to three experimental groups (n = 8/group): the control group, the NSAIDs group receiving indomethacin to induce gastric ulcers, and the NSAIDs with GJE pretreatment (NSAIDs + GJE) group. After a two-day experimental period, the stomachs were collected for histopathological examination, immunohistochemical staining, and protein expression analysis in gastric tissue lysates. Results The NSAIDs group exhibited severe neutrophil infiltration with ulcers upon gastric histopathological examination. Pretreatment with GJE attenuated NSAID-induced gastropathy, as evidenced by reduced neutrophil infiltration and decreased ulceration. Immunohistochemical staining and Western blotting demonstrated reduced expressions of PGE2 and MUC5AC, while the expressions of iNOS and NF-κB were increased following NSAID administration. In comparison to the NSAIDs group, the NSAIDs + GJE group exhibited higher expressions of PGE2 and MUC5AC and lower expressions of iNOS and NF-κB, providing evidence of the gastroprotective effects of GJE. Conclusions Pretreatment with GJE alleviated NSAID-induced gastric ulcers by increasing the expression of PGE2 and MUC5AC and decreasing the expression of iNOS and NF-κB. This study contributes to the understanding of the mechanisms by which GJE attenuates NSAID-induced gastropathy. Further studies are required to validate the effect of GJE in clinical settings.